2020
DOI: 10.1155/2020/7834173
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Hemadsorption versus Glucocorticoids during Cardiopulmonary Bypass: A Prospective, Randomized, Controlled Trial

Abstract: Extracorporeal hemadsorption may reduce inflammatory reaction in cardiopulmonary bypass (CPB) surgery. Glucocorticoids have been used during open-heart surgery for alleviation of systemic inflammation after CPB. We compared intraoperative hemadsorption and methylprednisolone, with usual care, during complex cardiac surgery on CPB, for inflammatory responses, hemodynamics, and perioperative course. Seventy-six patients with prolonged CPB were recruited and randomized, with 60 included in final analysis. Allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
4
25
2
Order By: Relevance
“…Our results show no significant difference in mortality and overall survival with the use of CytoSorb in LVAD implantation. Taleska Stupica et al also reported 1‐year mortality of their patients receiving CytoSorb not be significantly different when compared to the control group 14 . Nevertheless, unlike the previously mentioned randomized control trials, we found that patients treated with CytoSorb were more likely to develop respiratory failure, need mechanical ventilation for longer than 6 days post‐implant, and require tracheostomy during hospitalization.…”
Section: Discussioncontrasting
confidence: 67%
“…Our results show no significant difference in mortality and overall survival with the use of CytoSorb in LVAD implantation. Taleska Stupica et al also reported 1‐year mortality of their patients receiving CytoSorb not be significantly different when compared to the control group 14 . Nevertheless, unlike the previously mentioned randomized control trials, we found that patients treated with CytoSorb were more likely to develop respiratory failure, need mechanical ventilation for longer than 6 days post‐implant, and require tracheostomy during hospitalization.…”
Section: Discussioncontrasting
confidence: 67%
“…There are one systematic review [ 67 ], one multicenter RCT [ 68 ], five single-center RCTs (one ongoing) [ 69 73 ], and three related published studies [ 74 76 ]. In the systematic review published in 2021, except two RCTs investigating the application of extracorporeal cytokine adsorption therapy as a therapeutic add-on treatment in sepsis or septic shock, the other five RCTs investigated the application of CytoSorb as a preventive measure in cardiac surgery from 2016 to 2019.…”
Section: Evidence For the Application Of Cytosorb During Cpb Surgerymentioning
confidence: 99%
“…Systemic corticosteroids may have a potential pivotal role in the management of these patients; as reported by Xiang et al ( 22 ) they improve severe COVID-19 by reducing IL-6 levels and activating ACE2. Interesting findings from a randomized control trial evidenced the effectiveness of corticosteroids during CPB to reduced IL-6 expression ( p < 0.001) until 48 h after surgery compared to controls and extracorporeal hemadsorption ( 23 ). Others anti-inflammatory strategies, in severe COVID-19 undergoing cardiac surgery, could be the use of leukodepleting filters or IABP-induced pulsatile perfusion ( 24 , 25 ) as in the past the use of technical alterations such as heparin coating of the CPB circuit ( 26 ).…”
Section: Discussionmentioning
confidence: 99%